Romain Gary’s collaborative self-translations: Translational beyond translation - Kelbert, Eugenia (Meta, 2023)
This article considers the possibility of translational processes beyond translation through a genetic editing approach to an understudied phenomenon in Translation Studies, namely the use of intermediary allograph translations in collaborative self-translation. It considers a self-translator’s practice of involving a hired translator to provide an initial translation of an entire work, later to be revised extensively by the author. With a focus on Romain Gary as its case study, it argues that an inductive extension of our notion of what is translational can offer a pathway to distinguishing between literal and metaphorical use of translation in literary theory. It thus suggests a potential alternative to existing translational discourse in interdisciplinary settings, as well as presenting a view of collaborative self-translation as a practice that can be fruitfully theorised within multiple paradigms in Translation Studies.